A proposed analytical approach to estimate excess daily mortality rates in Ecuador - Fernandez-Naranjo, Raul Patricio; Vasconez-Gonzalez, Jorge; Izquierdo-Condoy, Juan S.; Landazuri, Samanta; Castillo, Diana; Ortiz-Prado, Esteban (Frontiers in Public Health, 2024)
The COVID-19 pandemic has been deadly globally; however, one of the most lethal outbreaks worldwide occurred in Ecuador.Aims: This study aims to highlight the pandemic's impact on the most affected countries worldwide due to the pandemic in terms of excess deaths per capita and per day.Methods: An ecological study of all-cause mortality recorded in Ecuador was performed. To calculate the excess death relative to the historical average for the same dates in 2017, 2018 and 2019 we developed a bootstrap method based on central tendency measure, mean. A Poisson fitting analysis was used to identify trends on officially recorded all-cause deaths and COVID-19 deaths. A bootstrapping technique was used to emulate the sampling distribution of our expected deaths estimator 𝝁 ̂𝒅𝒆𝒂𝒕𝒉𝒔 by simulating the data generation and model fitting processes daily since the first confirmed case.In Ecuador, during 2020, 115,070 deaths were reported and 42,453 were catalogued as excess mortality when comparing to 2017-2019 period. Ecuador is the country with the highest recorded excess mortality in the world within the shortest timespan compared to countries like Germany, Chile, Peru and Bolivia. In one single day, Ecuador recorded 1,120 deaths (6/100,000), represents an additional 408% of the expected fatalities.Adjusting for population size and time, the hardest-hit country due to COVID-19 pandemic was Ecuador. The mortality excess rate shows that the SARS-CoV-2 virus spread rapidly in Ecuador, especially in the coastal region. Our results and the proposed new methodology could help to address the real situation of the number of deaths during the initial phase of pandemics.